Shyam Selvadurai’s Funny Boy in Sinhala and French: Translating Culture-Bound Terms - JAYAWARDENA, Samanthi (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
Translating culture-bound terms presents numerous challenges to translators. The current study looks at how translators deal with this challenge in their respective target languages. The study includes Shyam Selvadurai's Sri Lanka-set Funny Boy and two of its translations, Drôle de garçon (1998) and Amuthu ilandariya (2002). According to Newmark's (2003) classification, three cultural categories are identified. Aixelà’s (1996) taxonomy of strategies to translate culture-bound terms is applied to the chosen cultural categories. The culture-bound terms and their translations are analysed to identify the strategies employed by the translators and then compared to discover similarities and differences in their practises. The results reveal that in each cultural category, the translators favour a combination of strategies. There is a strong tendency towards foreignizing strategies rather than domestication strategies. Problems that arise as a result of implementing these strategies are also discussed